2020
DOI: 10.3390/en13061309
|View full text |Cite
|
Sign up to set email alerts
|

Application of Rough Set Theory (RST) to Forecast Energy Consumption in Buildings Undergoing Thermal Modernization

Abstract: In many regions, the heat used for space heating is a basic item in the energy balance of a building and significantly affects its operating costs. The accuracy of the assessment of heat consumption in an existing building and the determination of the main components of heat loss depends to a large extent on whether the energy efficiency improvement targets set in the thermal upgrading project are achieved. A frequent problem in the case of energy calculations is the lack of complete architectural and construc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 42 publications
(61 reference statements)
0
19
0
Order By: Relevance
“…Finally, the set economic costs of thermo-modernization E ekon are summarized (Table 12) for the same eight thermo-modernization variants and for both buildings as in the case of ecological analysis. Similarly, variants (1) and (2) relate only to boiler replacement, variants (3) and (4) are associated with the very implementation of thermal insulation, and variants (5) to (8) are associated with boiler replacement and thermal insulation. Unfortunately, the economic costs of thermo-modernization came out positive in all variants.…”
Section: Mathematical Model For Determining Economic Costs Associatedmentioning
confidence: 99%
See 3 more Smart Citations
“…Finally, the set economic costs of thermo-modernization E ekon are summarized (Table 12) for the same eight thermo-modernization variants and for both buildings as in the case of ecological analysis. Similarly, variants (1) and (2) relate only to boiler replacement, variants (3) and (4) are associated with the very implementation of thermal insulation, and variants (5) to (8) are associated with boiler replacement and thermal insulation. Unfortunately, the economic costs of thermo-modernization came out positive in all variants.…”
Section: Mathematical Model For Determining Economic Costs Associatedmentioning
confidence: 99%
“…This means that the economic costs of using the building will increase as a result of such a thermo-modernization investment. The lowest economic costs of thermo-modernization were obtained for variants (3) and (4), in which only thermal insulation is provided, both for the building B 1 and B 2 .…”
Section: Mathematical Model For Determining Economic Costs Associatedmentioning
confidence: 99%
See 2 more Smart Citations
“…These activities also include modernization and replacement of heat sources, replacement of windows and modernization of internal heating systems. In Polish conditions, according to the research carried out on a group of 109 multi-family residential buildings, for which energy characteristics were determined, based on actual energy consumption before and after thermal improvement, it was indicated that thanks to comprehensive thermomodernization, savings of 38-40% can be achieved [11], such a level of savings can be described as "average" [12,13]. Therefore, it is advisable to use other instruments to improve energy efficiency, through modernization and improvement of heat management-operational regulation in heating systems of buildings.…”
Section: Introductionmentioning
confidence: 99%